ALABALIĞIN YENİ TİP GÜNEŞLİ KURUTUCUDA KURUTULMASINDA ISI VE KÜTLE TRANSFERİ - BİLGİÇ, YUSUF (Fırat Üniveristesi, 2014)
Bu çalışmada güneş enerjili kurutucuda alabalığın kurutulması deneysel olarak incelenmiştir. Çalışma üç aşamada gerçekleştirilmiştir. İlk önce güneş enerjili havalı kolektörün deneysel olarak incelenmiştir. Kolektörlerin incelemesi yapılırken 5 farklı tip kolektör kullanılmıştır. Termodinamiğin I. ve II. Kanuna göre verimleri incelenmiştir. I. Kanun verimi en yüksek olan kolektör kurutma işleminde kullanılmıştır. Kurutma işlemi 2,3 ve 4 m/s'lik hava hızlarında yapılmıştır. Daha sonraki aşamada hem hız hem de sıcaklık sabitlenmiştir. Sıcaklığı sabitlemek için elektrikli bir ısıtıcı kullanılmıştır. Deneyler 3,4 ve 5 m/s'lik sabit hızlarda; 50,60 ve 70 oC'lik sabit sıcaklıkta yapılmıştır. Deneylerde kuruma havasının hızının, sıcaklığının, alabalığın tuzda bekletilmesinin ve balığın boyutunun etkisi incelenmiştir. Kurutma deneyleri sonucuna göre nem içeriği, boyutsuz nem oranı ve kuruma hızları hesaplanmıştır. Bu sonuçlar grafiklere aktarılmıştır. Kuruma eğrilerinin matematiksel modelleri yapılmıştır. Her bir durum için

In this study, drying process of a trout in a solar drier was experimentally investigated. The study was carried out in three stages. At the beginning, solar powered air collector was experimentally analysed. In the analysis, five different types of the collectors were taken into consideration. The efficiencies of the collectors were estimated according to first and second laws of thermodynamics. The collector, having the highest efficiency regarding to first law, was chosen for the drying process. Experiments were conducted at the air velocities of 2.3 and 4m/s for drying process. In the next steps, both the temperature and velocity were kept constant. An electrical resistance was put account in order to stabilize the speed. Experiments were accomplished at the constant velocities of 3.4 and 5m/s, constant temperatures of 50, 60 and 70oC. Effects of the air speed, temperature, hold of the trout in the salt and trout sizes on the drying process were researched. Moisture content, dimensionless humidity and drying velocity were calculated with respect to results obtained from drying experiments and the data were turned into graphical representations. Mathematical models were proposed to drying curves and diffusion coefficients were computed for each case. At the final stage, the exergy analysis of the drier was evaluated.
Heat and mass transfer of the drying process of trout in a new type solar drier
Keywords: Makine Mühendisliği